2019
DOI: 10.1155/2019/4040236
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in the Evaluation of Osteochondral Lesion Treatments: Histology, Histomorphometry, and Biomechanics in Preclinical Models

Abstract: Osteochondral lesions (OCs) are typically of traumatic origins but are also caused by degenerative conditions, in primis osteoarthritis (OA). On the other side, OC lesions themselves, getting worse over time, can lead to OA, indicating that chondral and OC defects represent a risk factor for the onset of the pathology. Many animal models have been set up for years for the study of OC regeneration, being successfully employed to test different treatment strategies, from biomaterials and cells to physical and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 81 publications
1
27
0
1
Order By: Relevance
“…Here we used a surrogate to measure the quality of repaired cartilage - biomechanical property. Previous studies measuring cartilage biomechanical features involve separation of cartilage layer that are destructive 2 . Measurement of isolated cartilage suffers being destructive and inaccuracy in reflection of the property of articular cartilage in its native setting in the joint.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here we used a surrogate to measure the quality of repaired cartilage - biomechanical property. Previous studies measuring cartilage biomechanical features involve separation of cartilage layer that are destructive 2 . Measurement of isolated cartilage suffers being destructive and inaccuracy in reflection of the property of articular cartilage in its native setting in the joint.…”
Section: Discussionmentioning
confidence: 99%
“…The technique employed in our study is a desirable measurement since it is nondestructive and measures cartilage biomechanical property with a subchondral bone as a single unit 9 . Indentation with a force to the intact cartilage surface in fresh tissue simulates in vivo situation 2 , 9 . It has been shown that indentation measurement of articular cartilage correlates with histological scores and biomechanical properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…J o u r n a l P r e -p r o o f chondrogenicity of engineered tissues, only qualitative manual scoring systems 8,11 . Today, deep learning methods are increasingly being used for biomedical image analysis and are widely available to researchers.…”
Section: Introductionmentioning
confidence: 99%